Translation and validation of the Indonesian version of the seek counseling inventory for adolescents - Juniarni, Lia; S Kanathasan, Jayasree; Nallappan, Devi (The Journal of Palembang Nursing Studies, 2025)
Background: Adolescents in Indonesia encounter a range of psychological and social challenges, including stress, anxiety, and academic pressures. However, cultural stigma and traditional beliefs often hinder their willingness to access mental health services. Reliable and culturally appropriate assessment tools are essential to evaluate adolescents’ readiness to seek counseling and to identify barriers that may prevent timely intervention. Objective: This study aimed to translate and culturally adapt the Seek Counseling Inventory (SCI) into Indonesian and to evaluate its psychometric properties, ensuring its suitability for use among Indonesian adolescents. Methods: A systematic cross-cultural adaptation process was conducted, involving forward translation, back-translation, expert panel review, and pretesting. Content validity was assessed by a panel of five experts using Aiken’s V, while construct validity was examined through Confirmatory Factor Analysis (CFA). The study recruited 435 high school students aged 13–18 years through convenience sampling. Reliability was evaluated using Cronbach’s alpha. Results: The Indonesian version of the SCI demonstrated strong content validity, with Aiken’s V scores ranging from 0.80 to 1.00. CFA results indicated an acceptable model fit (TLI = 0.976, CFI = 0.947, RMSEA = 0.051), supporting the instrument’s structural validity. Internal consistency was good, with a Cronbach’s alpha of 0.822, indicating stable and coherent measurement of counseling attitudes. Conclusions: The Indonesian SCI is a valid and reliable tool for assessing counseling attitudes among adolescents. Its application can guide culturally sensitive mental health programs, enhance early identification of support needs, and contribute to reducing stigma toward counseling in Indonesia.